Determinants of troponin release in patients with stable coronary artery disease: insights from CT angiography characteristics of atherosclerotic plaque - Korosoglou, Grigorios; Lehrke, Stephanie; Mueller, Dirk; Hosch, Waldemar P.; Kauczor, Hans-Ulrich; Humpert, Per Magnus; Giannitsis, Evangelos; Katus, Hugo (Heart, 2011)
Objective To understand the determinants of troponin release in patients with stable coronary artery disease (CAD) by comparing high sensitive troponin T (hsTnT) levels with computed tomography angiography (CTA) characteristics of atherosclerotic plaque. - Methods hsTnT was determined in 124 consecutive patients with stable angina, who underwent clinically indicated 256-slice CTA for suspected CAD. CTA was used to assess (1) coronary calcification; (2) stenosis severity; (3) non-calcified plaque volume; (4) plaque composition (soft or mixed, described as ‘non-calcified’ versus calcified) and (5) the presence of vascular remodeling in areas of non-calcified plaque. - Results All CT scans were performed without adverse events, and diagnostic image quality was achieved in 1830/1848 available coronary segments (99.0%). In 29/124 patients, hsTnT was ≥14 pg/ml (range 14.0-34.4). Weak, albeit significant, correlations were found between hsTnT and calcium scoring (r=0.45, p<0.001), while a stronger correlation was found between hsTnT and the total non-calcified plaque burden (r=0.79, p<0.001). Patients with non-calcified plaque (n=44) yielded significantly higher hsTnT values than those with normal vessels (n=46) or those with only calcified lesions (n=26), (12.6±5.2 vs 8.3±2.6 and 8.8±3.0 pg/ml, respectively, p<0.001). Furthermore, those with remodeled non-calcified plaque (n=8) showed even higher hsTnT values of 26.3±6.5 pg/ml than all other groups (p<0.001). This allowed the identification of patients with remodeled non-calcified plaque by hsTnT with high accuracy (area under the curve=0.90, SE=0.07, 95% CI 0.84 to 0.95). - Conclusions Chronic clinically silent rupture of non-calcified plaque with subsequent microembolisation may be a potential source of troponin elevation. In light of recent imaging studies, in which patients with positively remodeled non-calcified plaque were shown to be at high risk for developing acute coronary syndromes, hsTnT may serve as a biomarker for such ‘vulnerable’ coronary lesions even in presumably stable CAD.
Gesehen am 07.07.2022